Turnover of "PPP1R15A" mRNA encoding GADD34 controls responsiveness and adaptation to cellular stress - Magg, Vera; Manetto, Alessandro; Kopp, Katja; Wu, Chia Ching; Naghizadeh, Mohsen; Lindner, Doris; Eke, Lucy; Welsch, Julia; Kallenberger, Stefan M.; Schott, Johanna; Haucke, Volker; Locker, Nicolas; et al. (Cell reports, 2024)
The integrated stress response (ISR) is a key cellular signaling pathway activated by environmental alterations that represses protein synthesis to restore homeostasis. To prevent sustained damage, the ISR is counteracted by the upregulation of growth arrest and DNA damage-inducible 34 (GADD34), a stress-induced regulatory subunit of protein phosphatase 1 that mediates translation reactivation and stress recovery. Here, we uncover a novel ISR regulatory mechanism that post-transcriptionally controls the stability of PPP1R15A mRNA encoding GADD34. We establish that the 3′ untranslated region of PPP1R15A mRNA contains an active AU-rich element (ARE) recognized by proteins of the ZFP36 family, promoting its rapid decay under normal conditions and stabilization for efficient expression of GADD34 in response to stress. We identify the tight temporal control of PPP1R15A mRNA turnover as a component of the transient ISR memory, which sets the threshold for cellular responsiveness and mediates adaptation to repeated stress conditions.